2019
DOI: 10.1101/749226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An assessment of LRRK2 serine 935 phosphorylation in human peripheral blood mononuclear cells in idiopathic Parkinson’s disease and G2019S LRRK2 cohorts

Abstract: The phosphorylated form of LRRK2, pS935 LRRK2, has been proposed as a target modulation biomarker for LRRK2 inhibitors. To qualify the biomarker for therapeutic trials, we assessed pS935 LRRK2 levels in Peripheral Blood Mononuclear Cells (PBMCs).Analyses of PBMCs from healthy controls, idiopathic Parkinson's disease (iPD), and G2019S carriers with and without PD showed significant reductions in pS935 LRRK2 levels normalized to total LRRK2 levels in G2019S carriers with PD compared to those without PD or iPD. N… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…One intriguing observation from our analysis is that phosphorylation of Ser935 in GSKI brain lung and kidney is reduced by ~half. These results were not observed in cell lines [ 9 ] but are in line with two recent papers where pSer935 was reported to be reduced in peripheral blood mononuclear cells (PBMCs) of disease-manifesting G2019S carriers compared to idiopathic PD or controls [ 48 , 49 ], overall supporting the GSKI mouse with endogenous mutant Lrrk2 expression as a valuable pre-symptomatic model of disease. Since overexpression of RAB29 was observed to reduce Ser935 phosphorylation in both WT and G2019S LRRK2 [ 39 ], one possibility is that the decreased phospho-Ser935 observed in GSKI tissues is due to increased RAB29-dependent recruitment.…”
Section: Discussionsupporting
confidence: 84%
“…One intriguing observation from our analysis is that phosphorylation of Ser935 in GSKI brain lung and kidney is reduced by ~half. These results were not observed in cell lines [ 9 ] but are in line with two recent papers where pSer935 was reported to be reduced in peripheral blood mononuclear cells (PBMCs) of disease-manifesting G2019S carriers compared to idiopathic PD or controls [ 48 , 49 ], overall supporting the GSKI mouse with endogenous mutant Lrrk2 expression as a valuable pre-symptomatic model of disease. Since overexpression of RAB29 was observed to reduce Ser935 phosphorylation in both WT and G2019S LRRK2 [ 39 ], one possibility is that the decreased phospho-Ser935 observed in GSKI tissues is due to increased RAB29-dependent recruitment.…”
Section: Discussionsupporting
confidence: 84%
“…A recent report assessed changes in pS935-LRRK2 in PBMCs from the same cohort using a proprietary ELISA, based on the Simoa platform. 15 This report showed a statistically significant decrease in pS935-LRRK2 in G2019S-positive PD patients compared to iPD. One possibility for the difference between this report and our current study could be related to the different capture antibodies used in the two studies (rabbit monoclonal, clone c41-2 here, vs. mouse monoclonal clone N241A in the Simoa assay).…”
Section: Discussionmentioning
confidence: 61%
“…A recent report assessed changes in pS935‐LRRK2 in PBMCs from the same cohort using a proprietary ELISA, based on the Simoa platform 15 . This report showed a statistically significant decrease in pS935‐LRRK2 in G2019S‐positive PD patients compared to iPD.…”
Section: Discussionmentioning
confidence: 99%
“…The search for a sensitive and high throughput assay to detect LRRK2 and/or pLRRK2 levels in CSF has been a challenge for both academic investigators and industry teams seeking to advance clinical stage LRRK2 therapeutic programs. Our internal work suggested that a number of high quality antibody reagents could be used to develop ultrasensitive immunoassays (e.g., Quanterix Simoa, Sinuglex Erenna, MSD S-plex) that could measure low pg/ml concentrations (Biogen Internal; Padmanabhan et al, 2020). Although those assays performed well in tissues such as rodent and primate brain and human PBMCs, they could not reliably detect LRRK2 in human CSF with or without exosome isolation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of high quality total LRRK2 mAbs and commercially available ELISA kits are available, however, to date there have been no reports demonstrating reliable CSF LRRK2 detection with these. Internal efforts from Biogen and other industry groups with support from the MJFF have developed ultrasensitive immunoassays (Singulex Erenna, Quanterix Simoa, MSD S-plex) to enable CSF LRRK2 detection (Padmanabhan et al, 2020). Despite single digit pg/ml sensitivity limits, and robust detection in rodent and primate tissues these assays were unable to reliably detect LRRK2 in human CSF (unpublished internal Biogen data).…”
Section: Introductionmentioning
confidence: 99%